Direct‐acting antivirals for HCV treatment in older patients: A systematic review and meta‐analysis. Issue 11 (17th July 2019) - Villani, Rosanna; Monami, Matteo; Di Cosimo, Francesca; Fioravanti, Gilda; Mannucci, Edoardo; Vendemiale, Gianluigi; Serviddio, Gaetano
Abstract: The advent of highly effective and well‐tolerated direct antiviral antivirals (DAAs) has dramatically changed the landscape of chronic hepatitis C. The effect of DAAs in older adults is difficult to determine since patients aged ≥ 65 years were too few in most clinical trials and data mainly come from observational studies. We performed a systematic review and meta‐analysis to evaluate the efficacy and safety of DAAs in patients aged 65 and older. PubMed, Scopus, Web of Science, Cochrane Central Register of Controlled Trials, ClinicalTrials.gov, HCV‐Trials.com databases were searched for literature published until 1 December 2017. English language articles reporting results of phase 2 or 3 randomized controlled trials (RCTs), single‐arm clinical trials (SATs) and observational studies were included in the final analysis. All studies included subgroups of older patients and compared their outcomes with younger individuals. By using a random‐effects or fixed‐effects model, odds ratio (OR) was calculated for the efficacy and safety. Heterogeneity was tested using I 2 statistics. Thirty‐seven studies reported data on the DAA efficacy. The OR was 1.66 (95%CI: 1.00‐2.75; P  = 0.06) in meta‐analysis of RCTs, and similar results were found in SATs and observational studies. HCV genotype, stage of fibrosis or HIV co‐infection did not affect the rate of SVR in older persons. Prevalence of anaemia (OR 0.26 95%CI: 0.09‐0.69; P  = 0.007) (OR 0.25 95%CI: 0.09‐0.69; P = 0.007) and skin complaints (OR 0.61 95%CI: 0.45‐0.83; P  = 0.001) was higher in older adults. Finally, geriatric patients affected by chronic HCV infection can be safely treated with DAAs with the same efficacy reported in younger adults.